A STUDY ON EMPLOYEE ENGAGEMENT IN CHETTINAD CEMENT CORPORATION LIMITED, PULIYUR, KARUR - CHADRASEKARAN, Dr.M.; VANITHAMANI, A. (IJRDO - Journal of Applied Management Science, 2017)
Employee engagement is the important drive in an organization to achieve their premier goal. Engagement is an employees’ involvement with deep interest in the organization’s principles. In business context, employee engagement is refer to work with colleagues to get effective task performance which leads to productivity of the organization. To understand the levels of employee engagement and its impact is the core objectives of this paper and further to examine the various factors influencing the employee engagement. This research paper suggests the effective ways to improve the productivity by applying the better strategies of employee engagement.